Nanoconfined Nitrogen‐Doped Carbon‐Coated Hierarchical TiCoN Composites with Enhanced ORR Performance. Issue 14 (19th June 2018) - Tang, Haibo; Luo, Junming; Yu, Jinnan; Zhao, Weiyue; Song, Huiyu; Liao, Shijun
Abstract: The high cost of platinum‐based cathode catalysts for the oxygen reduction reaction (ORR) has long hampered the practical application of fuel cells. In‐depth studies have shown titanium nitride (TiN) is an interesting non‐precious‐metal electrocatalysts for replacing Pt, due to their low cost, excellent catalytic properties, and stability. In this study, we report on a three‐dimensional (3D) nitrogen‐doped carbon‐coated hierarchical Ti0.95 Co0.05 N composite, created using a one‐step impregnation method followed by nitriding. The catalyst exhibited significantly enhanced ORR activity and excellent electrochemical stability. Our optimal catalyst, 20 %C‐Ti0.95 Co0.05 N, had an ORR performance almost comparable to 20 % Pt/C in an alkaline medium, and a four‐electron pathway was dominant during the ORR reaction. The significantly enhanced ORR performance of this catalyst is attributable to the following factors: the synergic effect of a carbon coating on the nitride nanoparticles (NPs), including the higher surface area and more exposed active‐sites caused by the well‐defined 3D structure resulting from the carbon coating; better mass transfer and electron transfer due to the carbon coating; the contribution of the doped carbon; and enhancement of the nitride's activity by doping with transition metal. Abstract : Synergistic confinement : non‐precious‐metal electrocatalysts for the oxygen reduction reaction in fuel cells are urgently required to replace currently used Pt based materials. Towards this goal, a three‐dimensional nitrogen‐doped carbon‐coated hierarchical Ti0.95 Co0.05 N composite is created using a one‐step impregnation method followed by nitriding. The catalyst exhibits enhanced ORR activity and excellent electrochemical stability.